The Role Of Customer Satisfaction As An Intervening Variable Mediating The Influence of Service Quality And Product Quality On Customer Loyalty - Elyzzatul Aini; Siswanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses customer satisfaction which is a mediating variable on the influence of service quality and product quality on customer savings loyalty at Bank Muamalat Indonesia Malang Branch Office. The research method used is a quantitative approach with Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis. The research results show that service quality has no significant effect on consumer loyalty, while product quality has a positive and significant effect. Both service quality and product quality have a positive and significant effect on consumer satisfaction. Customer satisfaction plays a positive and significant role in building customer loyalty. Fully mediates customer satisfaction in the relationship between service quality and customer loyalty. Meanwhile, customer satisfaction partially mediates the relationship between product quality and customer loyalty. The implication of this research is that Bank Muamalat Indonesia KC Malang needs to maintain and improve product quality and customer satisfaction to strengthen customer savings loyalty. Apart from that, improving service quality is also needed to increase customer satisfaction and loyalty.